(3GdgjFIs - (3LGHQ Hf GadM (B( (3GdCadM (B) (3GdGTHjdjs
(3ChdgG (B:s
(3GdMeO ddg GdChd HdG GHJOGA hGdGNQ HdG GfJgGA hcGf HWdjehS GdbdhRi bO LeY eG GOQcI GdbOeGA bHdg hGVGa Gdjg eG GOQcg gh HYOge s
(3BNQgG (B:s
(3HYO ehVY GdbeQ GdMbjbi GdHQhL ef SeJ GdQCS eYdheI hgj fgGjI YQV GdbeQ eYdheI Ke HjGfg ced GdcJGH HMeO Gddg hMSf Yhfg s
(3HgG LOGhd hCTcGd gfOSjI cKjQIs
(3fSNI fajSIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B469s
Keywords: (3Gdadcs